Virtual Hybrid Synthesizer Application - Yoga, I Putu Harta; Giri, S.Kom., M.Cs., Gst. Ayu Vida Mastrika (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 8 No 3 (2020): JELIKU Volume 8 No 3, February 2020, 2020)
Hybrid synthesizers can be syntheses with digital or analog signals on a hardware device. In this article hybrid means make a virtual digital synthesis which combines several synthesis methods. The method used is the synthesis method of additive, substractive, and amplitude modulation (AM). Where the initial signal is an oscillator by making waves with the form Sinusoide Wave, Square Wave and Saw Tooth Wave. This virtual synthesis produces sound that has the same fundamental frequency as the fundamental frequency of notes. Keywords: Hibrid Synthesizer, Additive, Substractive, Amplitude Modulation